Reading the Odyssey: a guide to Homer’s narrative - Grethlein, Jonas (Princeton University Press, 2024)
A fresh and original introduction to the Odyssey—and how it continues to shape literature, film, art and even the ways we make sense of our livesReading the Odyssey is an introduction to Homer’s masterpiece like no other. It combines a cultural and intellectual history of the epic with an in-depth exploration of its unique and influential narrative structure and the ways it continues to inform issues of identity, meaning and experience.Reading the Odyssey begins with a broad history of the epic’s reception and interpretation, its place in cultural and intellectual history and its influence today on literature, film and art. After introducing the literary form of the Odyssey, the book turns to its main focus: the layered narrative that lies at the heart of the poem. Taking readers on a tour of the epic, Jonas Grethlein shows the nuanced ways the Odyssey uses a wide variety of narrative forms and functions. At the same time, he highlights how we all rely on narratives, first used by Homer, to form identities, forge communities and make sense of our lives.The result is a compelling guide to the Odyssey that demonstrates why it continues to speak so powerfully to so many readers today